Early diagnosis of coxitis in ankylosing spondylitis - Sh. F. Erdes; E. M. Agafonova; T. V. Dubinina; A. B. Demina; A. V. Smirnov (Современная ревматология, 2023)
Coxitis is one of the characteristic clinical manifestations of ankylosing spondylitis (AS). Hip joint (HJ) involvement in AS is considered an un-favorable prognostic factor. Early detection of coxitis is of great importance, since with the timely initiation of adequate treatment, the risk of developing irreversible changes in HJ can be reduced.The lecture discusses the issues of clinical and instrumental diagnosis of coxitis in AS and presents an algorithm for its early detection developed by the authors.